The development, implementation and evaluation of a father inclusive perinatal support intervention to increase breastfeeding duration : a randomised controlled trial - Tohotoa, Jennifer Lynn (Curtin University, 2012)
Breastfeeding is the biological norm for infant feeding and the most efficient and cost-effective method of giving the required nutrition to infants. The World Health Organization, the American Academy of Paediatrics and the National Health and Medical Research Council recommend exclusive breastfeeding for six months and the continuation of complementary foods for up to two years. Although most developed countries maintain high initiation rates, the duration rates fail to meet these recommendations. The promotion of breast milk substitutes, changing societal values, urbanization, and the erosion of traditional support systems pose threats to breastfeeding. In Australia the breastfeeding initiation rates are between 85%-95% but fall to 20%-45% by six months. There is some evidence that fathers, the primary support to their partners, influence the initiation and maintenance of breastfeeding by their partners. There has been little research in this area, however, with little known about the nature of a father’s support required by the mother and few interventions have specifically targeted fathers.The present thesis describes the development, implementation and evaluation of a father inclusive perinatal support intervention at six weeks postnatal. The project was conducted over three years as a randomised controlled trial (RCT) across eight public maternity hospitals in Perth, Western Australia.